Doxorubicin-Induced Cardiotoxicity in Breast Cancer: Mechanistic Pathways, Pharmacogenomic Modifiers, and Translational Strategies - Chi-Tong Kuok; Hao-Wei Lee; Chen-Yu Huang; Yu-Che Cheng; Shih-Chang Lin; Jiun-Wen Guo (Cardiovascular Toxicology, 2026)

Synergistic LiNO3/FEC modification to nonflammable LiOTf-TMP electrolyte for durable lithium metal batteries - Chun-Jern Pan; Chia-Ho Liu; Shih-Che Lin; Chun-I Lee; Chia-Hsin Wang; Bing-Joe Hwang (Chemical Engineering Journal, 2026)

Generative data augmentation for AIoT-based smart pig farming: The PigTalk 2.0 system - Whai-En Chen; Shih-Che Lin; Hsin-Hung Cho (Computers and Electronics in Agriculture, 2026)

Structure–reactivity relationships in UV/chlorine degradation, NDMA formation, and cytotoxicity of chlorpheniramine and doxylamine - Shih-Wen Peng; Pei-Jin Lin; Ya-Hong Lin; Che-Hsin Lee; Yu-Chun Tseng; Ming-Cyuan He; Wei-Hsiang Chen (Journal of Hazardous Materials, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Interactions between turnover rate and bioactivity of atractylenolide III in Atractylodes macrocephala rhizome in the theory of crude drugs’ pairs and prescriptions in traditional Chinese and Japanese Kampo medicine - Pei-Ying Chou; Yung-Jia Chiu; Che-Chun Lin; Lih-Geeng Chen; Shih-Yi Hsiung; Toshiaki Makino; Ching-Chiung Wang (Journal of Natural Medicines, 2025)

Exploring couples’ information-seeking behaviors when faced with a rare tornado threat - Chih-Chun Lin; Shih-Kai Huang; Hao Zhang; Barend Stander; Hao-Che Wu; Haley Murphy (Natural Hazards, 2025)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

Enhanced mitigation of inhalable particles and fine particle-bound PAHs from a novel hazardous waste-power plant candidate - Wei Tang; Che-Wei Wu; Sheng-Lun Lin; Jhong-Lin Wu; Shih-Wei Huang; Mengjie Song (Environmental Pollution, 2024)

Anthropogenic nitrogen pollution inferred by stable isotope records of crustose coralline algae - Aafaq Nazir; Chiao-Feng Lai; Shih-Wei Wang; Showe-Mei Lin; Hong-Chun Li; Ming-Tsung Chung; Pei-Ling Wang; Yung-Che Tseng; Jen-Chieh Shiao (Marine Pollution Bulletin, 2024)

Edge-based wireless imaging system for continuous monitoring of insect pests in a remote outdoor mango orchard - Dan Jeric Arcega Rustia; Wei-Che Lee; Chen-Yi Lu; Ya-Fang Wu; Pei-Yu Shih; Sheng-Kuan Chen; Jui-Yung Chung; Ta-Te Lin (Computers and Electronics in Agriculture, 2023)

Clay nanosheets simultaneously intercalated and stabilized by PEGylated chitosan as drug delivery vehicles for cancer chemotherapy - Hsuan-Jung Huang; Shih-Yu Huang; Tzu-Hao Wang; Tzu-Yun Lin; Nan-Ching Huang; Orion Shih; U-Ser Jeng; Che-Yi Chu; Wen-Hsuan Chiang (Carbohydrate Polymers, 2023)

An innovative targeted therapy for fluoroscopy-induced chronic radiation dermatitis - Kai-Che Wei; Shih-Fan Lai; Wei-Lun Huang; Kuo-Chung Yang; Ping-Chin Lai; Wan-Ju Wei; Tsung-Hsien Chang; Yun-Chen Huang; Ya-Chuan Tsai; Shin-Chih Lin; Sun-Jang Lin; Shih-Chieh Lin (Journal of Molecular Medicine, 2022)
Fluoroscopy-induced chronic radiation dermatitis (FICRD) is a complication of fluoroscopy-guided intervention. Unlike acute radiation dermatitis, FICRD is different as delayed onset and usually appears without preexisting acute dermatitis. Unfortunately, the chronic and progressive pathology of FICRD makes it difficult to treat, and some patients need to receive wide excision and reconstruction surgery. Due to lack of standard treatment, investigating underlying mechanism is needed in order to develop an effective therapy. Herein, the Hippo pathway is specifically identified using an RNA-seq analysis in mild damaged skin specimens of patients with FICRD. Furthermore, specific increase of the Yes-associated protein (YAP1), an effector of the Hippo pathway, in skin region with mild damage plays a protective role for keratinocytes via positively regulating the numerous downstream genes involved in different biological processes. Interestingly, irradiated-keratinocytes inhibit activation of fibroblasts under TGF-β1 treatment via remote control by an exosome containing YAP1. More importantly, targeting one of YAP1 downstream genes, nuclear receptor subfamily 3 group C member 1 (NR3C1), which encodes glucocorticoid receptor, has revealed its therapeutic potential to treat FICRD by inhibiting fibroblasts activation in vitro and preventing formation of radiation ulcers in a mouse model and in patients with FICRD. Taken together, this translational research demonstrates the critical role of YAP1 in FICRD and identification of a feasible, effective therapy for patients with FICRD. Key messages • YAP1 overexpression in skin specimens of radiation dermatitis from FICRD patient. • Radiation-induced YAP1 expression plays protective roles by promoting DNA damage repair and inhibiting fibrosis via remote control of exosomal YAP1. • YAP1 positively regulates NR3C1 which encodes glucocorticoid receptor expression. • Targeting glucocorticoid receptor by prednisolone has therapeutic potential for FICRD patient.

Nanotechnology advances in pathogen- and host-targeted antiviral delivery: multipronged therapeutic intervention for pandemic control - Kai-Chieh Yang; Jung-Chen Lin; Hsiao-Han Tsai; Chung-Yao Hsu; Vicky Shih; Che-Ming Jack Hu (Drug Delivery and Translational Research, 2021)

Characterization and adsorption capacity of potassium permanganate used to modify activated carbon filter media for indoor formaldehyde removal - Shih-Cheng Hu; Ying-Chen Chen; Xin-Zhi Lin; Angus Shiue; Po-Hua Huang; Yen-Che Chen; Shu-Mei Chang; Chao-Heng Tseng; Bin Zhou (Environmental Science and Pollution Research, 2018)

Prototype Deep Brain Stimulation System with Closed-Loop Control Feedback for Modulating Bladder Functions in Traumatic Brain Injured Animals - En Jen; Chii-Wann Lin; Tsung-Hsun Hsieh; Yi-Chun Chiu; Tsung-Che Lu; Shih-Ching Chen; Meng-Chao Chen; Chih-Wei Peng (Journal of Medical and Biological Engineering, 2018)

Important Roles of Ring Finger Protein 112 in Embryonic Vascular Development and Brain Functions - Jen-Hui Tsou; Ying-Chen Yang; Ping-Chieh Pao; Hui-Ching Lin; Nai-Kuei Huang; Shih-Ting Lin; Kuei-Sen Hsu; Che-Ming Yeh; Kuen-Haur Lee; Chu-Jen Kuo; De-Ming Yang; Jiann-Her Lin; et al. (Molecular Neurobiology, 2017)

Disentangling the effects of isolation-by-distance and isolation-by-environment on genetic differentiation among Rhododendron lineages in the subgenus Tsutsusi - Chun-Lin Huang; Jui-Hung Chen; Chung-Te Chang; Jeng-Der Chung; Pei-Chun Liao; Jenn-Che Wang; Shih-Ying Hwang (Tree Genetics & Genomes, 2016)

Identification and characterization of the microRNA transcriptome of a moth orchid Phalaenopsis aphrodite - Ya-Ting Chao; Chun-Lin Su; Wen-Han Jean; Wan-Chieh Chen; Yao-Chien Alex Chang; Ming-Che Shih (Plant Molecular Biology, 2014)

Evacuees’ information sources and reentry decision making in the aftermath of Hurricane Ike - Chih-Chun Lin; Laura K. Siebeneck; Michael K. Lindell; Carla S. Prater; Hao-Che Wu; Shih-Kai Huang (Natural Hazards, 2014)

Benzodiazepine therapy in psychiatric outpatients is associated with deliberate self-poisoning events at emergency departments—a population-based nested case–control study - Hsin-I Shih; Ming-Chia Lin; Che-Chen Lin; Hsiang-Chin Hsu; Hsin-Ling Lee; Chih-Hsien Chi; Fung-Chang Sung; Yen-Jung Chang; Chia-Hung Kao (Psychopharmacology, 2013)

Global transcriptome analysis and identification of a CONSTANS-like gene family in the orchid Erycina pusilla - Ming-Lun Chou; Ming-Che Shih; Ming-Tsair Chan; Shih-Yi Liao; Chen-Tran Hsu; Yao-Ting Haung; Jeremy J. W. Chen; Der-Chih Liao; Fu-Hui Wu; Choun-Sea Lin (Planta, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Suburban atmospheric visibility sensing by an image degradation processor: model development and field test - Chin-Hsiang Luo; Kuo-Hung Lin; Che-Yen Wen; Shih-Hsuan Chiu; Chung-Shin Yuan; Shinhao Yang (International Journal of Remote Sensing, 2011)

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

Differential expression of genes encoding 1-aminocyclopropane-1-carboxylate synthase in Arabidopsis during hypoxia - Hsiao-Ping Peng; Ter-Yun Lin; Ning-Ning Wang; Ming-Che Shih (Plant Molecular Biology, 2005)

Phylogeography of Trochodendron aralioides (Trochodendraceae) in Taiwan and its adjacent areas - Shing‐Fan Huang; Shih‐Ying Hwang; Jenn‐Che Wang; Tsan‐Piao Lin (Journal of Biogeography, 2004)
Aim This paper described current phylogeographical patterns of chloroplastic DNA variation of Trochodendron aralioides , a temperate tree species, and inferred its possible refugium in Taiwan. This information was compared with the known phylogeographical pattern of subtropical tree species. Location A total of 24 populations were sampled including 20 from Taiwan, two each from the Ryukyus and Japan. Methods A haplotype network was constructed by computer program TCS, various parameters of genetic diversity were calculated and neutrality was tested by computer program DnaSP. To examine the similarity of genetic structure among populations, a maximum parsimony tree was reconstructed by computer program PAUP*. The results of isozyme of T. aralioides from a previous publication were incorporated into this study to infer the phylogeographical history. Results Nine haplotypes according to six substitutions, two indels and one inversion of the two cpDNA intergenic spacer fragments ( pet G‐ trn P and pet A‐ psb J) of T. aralioides were recognized. Genetic structure of the population of Japan is totally different from those of Taiwan and the Ryukyus. In Taiwan, the genetic structure was differentiated among populations revealed by G st = 0.700 and N st = 0.542, and the population genetics was clearly spatially structured. Two population groups were recognized. The first group was distributed islandwide and extended to the Ryukyus. The second group contained five of the seven known haplotypes, and was restricted to the area between latitude 24°46′ and 24°06′ N. Conclusions In Taiwan, north‐central area between latitude 24°46′ and 24°06′ N is potentially a refugium during the last glaciations. This finding is contradicted to subtropical species as Cyclobalanopsis glauca .